Assessment of Syrian Obstetric Care Providers Knowledge, Attitude, and Practice Towards Preconception Care and Associated Factors: An Online Cross-Sectional Study - Haidara Bohsas; Sarya Swed; Hidar Alibrahim; Bisher Sawaf; Wael Hafez (International Journal of Medical Students, 2023)
Background: Preconception care was instituted in 2013 by the World Health Organization (WHO) to promote more attention to pregnant women by medical staff. Preconception care attempts to optimize pregnancy outcomes and promote health by managing and treating variables that influence it. Obstetric care providers in LAMICs have been reported to have low levels of preconception care awareness. This study investigates the Knowledge, attitudes, and practice-related features of obstetric care providers in Syria's public health institutions about preconception care.